2010
DOI: 10.1007/s11010-010-0505-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of apoA-I-dependent lipid efflux from adipocytes and role of ABCA1

Abstract: Adipose tissue is a major reservoir of cholesterol and, as such, it may play a significant role in cholesterol homeostasis. The aims of this study were to obtain a quantitative characterization of apolipoprotein A-I (apoA-I)-dependent lipid efflux from adipocytes and examine the role of ATPbinding cassette transporter A1 (ABCA1) in this process. The rates of apoA-I-induced cholesterol and phospholipid efflux were determined and normalized by cellular protein or ABCA1 levels. In order to allow a comparative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 61 publications
1
15
0
4
Order By: Relevance
“…ABCA1 has been shown to regulate adipocyte cholesterol levels ( 7,8 ). However, the role of ABCA1 in adipocyte function with regard to body weight and glucose metabolism is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ABCA1 has been shown to regulate adipocyte cholesterol levels ( 7,8 ). However, the role of ABCA1 in adipocyte function with regard to body weight and glucose metabolism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also supported by our data because we observed that ABCA1-defi cient adipose tissue accumulates TGs and cholesterol in response to an HFHC diet. It has been shown in vitro that increased ABCA1-mediated cholesterol effl ux from adipocytes occurs following the stimulation of TG lipolysis ( 7,8 Decreased insulin sensitivity in peripheral tissues results in increased insulin secretion by the pancreas to compensate for this insulin resistance ( 30,31 ). Increased production of insulin may eventually lead to beta-cell failure and reduced insulin secretion ( 30,31 ).…”
Section: Adipocyte Abca1 Defi Ciency Impairs Glucose Tolerance Reducmentioning
confidence: 99%
See 2 more Smart Citations
“…АТР-связывающие трансмембранные транспортеры семейства АВС -ABCA1 и ABCG1, координирующие элиминацию холестерина из клеток, исключительно важны для регуляции содержания холестерина в адипоцитах [6,7]. ABCA1 участвует в биогенезе ЛПВП на этапе формирования незрелых частиц пре-b-ЛПВП, в то время как ABCG1 осуществляет насыщение холестерином зрелых ЛПВП [8].…”
Section: Introductionunclassified